The influence of internet and social media on purchasing decisions in Kuwait - Abdulkareem Al-Enezi, Khalid; Taha Alshaikhli, Imad Fakhri; AlDabbagh, SufyaSalim Mahmood (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This research aims to measure the role of social networks in influencing purchasing decisions among consumers in Kuwait; the research used the quantitative methods, and analytical the technique to get the results, and the research developed a measure to study the relationship between the variables to the study and selection of a sample of consumers of (100). The results indicated that the social networking variables (exchange of information, evaluation of product) possess influence on purchasing decisions. Furthermore, the results indicate that majority of respondents do their digital scanning more often before intend to go to the store. The unexpected results came from the question “traditional advertising (TV, Newspaper, Magazine, Billboards) are more effective than the social networking; 23% agreed, 36% said no, and 41% said sometimes. In light of these findings, the study made a series of recommendations; the most important are; The executives and sales representatives need to understand the benefits offered by social networks, and understand the advantages and functions and tools of social communication, and knowing how to apply them effectively and efficiently, and then use the appropriate social networking tool.